1998
DOI: 10.1002/(sici)1097-0223(199812)18:12<1294::aid-pd433>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ultrasonographic diagnosis of the cerebro–costo–mandibular syndrome: case report and review of the literature

Abstract: We present an antenatal ultrasonographic diagnosis of the cerebro–costo–mandibular syndrome. This rare dysmorphic disorder (only 51 cases have been reported to date) mainly associates defective costal development with features of the Pierre–Robin syndrome. The diagnosis is very often made at birth and the prognosis is very poor. Antenatal ultrasound examination may show a combination of orofacial and chest maldevelopment. In our case the diagnosis was made at 20 weeks' gestation during a routine ultrasound exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The only method using in prenatal diagnosis is ultrasonographic examination. Megier et al reported a case with CCMS diagnosed prenatally for the first time 8 . Polyhydramnios and a very unusual shape of the ribs were documented as ultrasonographic findings of CCMS 8,9 …”
Section: Discussionmentioning
confidence: 99%
“…The only method using in prenatal diagnosis is ultrasonographic examination. Megier et al reported a case with CCMS diagnosed prenatally for the first time 8 . Polyhydramnios and a very unusual shape of the ribs were documented as ultrasonographic findings of CCMS 8,9 …”
Section: Discussionmentioning
confidence: 99%
“…It is closely related to pathological processes observed during the development of the mandible. It is inevitable that alveolar structures will be affected in cases of micrognathia or retrognathic mandible (Megier et al, 1998; Rotten et al, 2002; Zalel et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Full text and images were not available Excluded (Özahi et al, 2002;Padovani et al, 1982;Surka et al, 1999) Information insufficient to judge the phenotype (insufficient description, unclear image, no full-chest image, no information on the survival length) Excluded (Blaas et al, 1993;Farriaux & Poupard, 1978;Feldman & Heyman, 1987;Kang et al, 1992;Morin et al, 2001;Tanyeri et al, 2018;Winter & Bloom, 1999) Causal mutations in other genes than SNRPB and hence not diagnosed as CCMS Excluded (Legare et al, 2017;Zeevaert et al, 2009) Costovertebral joint defects without rib gap Excluded (Neelam & Sudhir, 2021) No ribs or underdeveloped ribs in the fetus/too young gestational stage/ premature birth Excluded (Fidalgo-Alvarez et al, 1988;Hennekam & Goldschmeding, 1998;Ibba et al, 1997;Kirk et al, 1999;Lale et al, 2011;Megier et al, 1998;Sahyoun et al, 1998;Song et al, 1993) Reporting follow-up only/follow-up cases and new cases without sufficient information Excluded (Doyle, 1969;Schrander-Stumpel et al, 1996;van den Ende et al, 1998) Analyzed in this study (90 cases in 60 papers in total)…”
Section: Included or Excluded Referencesmentioning
confidence: 99%